2019
DOI: 10.1021/acscatal.9b03396
|View full text |Cite
|
Sign up to set email alerts
|

Baeyer–Villiger Monooxygenases: Tunable Oxidative Biocatalysts

Abstract: Pollution, accidents, and misinformation have earned the pharmaceutical and chemical industry a poor public reputation, despite their undisputable importance to society. Biotechnological advances hold the promise to enable a future of drastically reduced environmental impact and rigorously more efficient production routes at the same time. This is exemplified in the Baeyer–Villiger reaction, which offers a simple synthetic route to oxidize ketones to esters, but application is hampered by the requirement of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(172 citation statements)
references
References 367 publications
3
167
0
2
Order By: Relevance
“…S1A ). GxGxxxG motif has hitherto been used to indicate the presence of FAD which could as readily indicate flavin-monooxygenase-related enzymes [ 22 ]. However, YWWxTKN, and GDAAH motifs, covering approximate 80 amino acid residues, are unique among LgnC-like monooxygenases and as such these two motifs may be used as PCR probe to screen LgnC-like monooxygenase from uncurated genomic DNAs of available bacterial strains ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…S1A ). GxGxxxG motif has hitherto been used to indicate the presence of FAD which could as readily indicate flavin-monooxygenase-related enzymes [ 22 ]. However, YWWxTKN, and GDAAH motifs, covering approximate 80 amino acid residues, are unique among LgnC-like monooxygenases and as such these two motifs may be used as PCR probe to screen LgnC-like monooxygenase from uncurated genomic DNAs of available bacterial strains ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The conserved regions are anked by the two Rossmann fold sequence motifs (GXGXX[G/A]). 37 This strongly suggests that this protein is a typical Type I BVMO. The alignment showed that it possesses 86% sequence identity with a BVMO from Streptomyces coelicolor A3(2) (UniProt Accession No.…”
Section: Effect Of Addition Of a Co-solventmentioning
confidence: 92%
“…22 It was reported that PMSO shows lower biotoxicity compared to PMS which may be due to the hydrophobic nature of the latter as stated before. 22,37,38 Also, phenyl methyl sulfone was reported to be one of the pesticide metabolites that contribute to potential toxicity to soil bacteria. 39 As a result, it is thought to induce the reductase system and undergo deoxygenation once congured.…”
Section: Effect Of Addition Of a Co-solventmentioning
confidence: 99%
“…Baeyer-Villiger monooxygenases (BVMOs) are flavin-dependent enzymes that catalyze the conversion of ketones to esters [1,2]. Naturally, they enable the use of alternative carbon sources or the synthesis of various secondary metabolites by microorganisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, their use as alternatives to chemical Baeyer-Villiger catalysts, and their ability to also catalyze heteroatom oxidation, has driven much of the research over the past two decades. This has led the search for new and improved BVMOs to expand on the current substrate-scope, enhanced regio-, enantio-and stereospecificity/selectivity, as well as stability of these promising biocatalysts [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%